Pengaruh Tunjangan Kesejahteraan Dan Kesehatan Kerja Terhadap Kinerja Karyawan Di Mediasi Oleh Kepuasan Kerja Pada Badan Pengembangan Sumber Daya Manusia (BPSDM) PROVSU - Sahbillah Nur; Aulia Arief Nasution; Sopi Pentana (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
This type of research is associative research with a quantitative approach. This research was conducted at the Human Resources Development Agency (BPSDM) which is a State-Owned Enterprise (BUMN) which is engaged in human resource development activities. Located at Jl. Ngalengko No.1 Perintis, East Medan District, Medan City, North Sumatra, the sample of respondents in this study was adjusted to 100 people from all employees of the Medan Human Resources Development Agency (BPSDM), the source of the data used in this study are primary and secondary data, Sub Structure I Variable Welfare Allowance (X1) of 0.371 states that every 1% addition of Welfare Allowance will increase Job Satisfaction by 0.371 or 37.1%, and vice versa if Welfare Allowance decreases by 1% then Job Satisfaction is predicted to decrease by 0.371 or 37 ,1%. Occupational Health Variable (X2) of 0.113 states that for every 1% addition of Occupational Health, it will increase Job Satisfaction by 0.113 or 11.3%, and vice versa if Occupational Health decreases by 1% then Job Satisfaction will be predicted to decrease by 0.113 or 11.3 %. Sub Structure II Variable Welfare Allowance (X1) of 0.097 states that for every additional 1% of Welfare Allowance, it will increase Employee Performance by 0.097 or 09.7%, and vice versa if Welfare Allowance decreases by 1% then Employee Performance will be predicted to decrease by 0.097 or 09.7%. The Occupational Health variable (X2) of 0.101 states that for every 1% addition of Occupational Health, it will increase Employee Performance by 0.101 or 10.1%, and vice versa if Occupational Health decreases by 1% then Employee Performance will be predicted to decrease by 0.101 or 10.1 %. The Job Satisfaction Variable (Z) of 0.668 states that every additional 1% of Job Satisfaction will increase Employee Performance by 0.668 or 66.8%, and vice versa if Job Satisfaction decreases by 1% then Employee Performance will be predicted to decrease by 0.668 or 66.8% .